Análisis integral del marco normativo colombiano en materia de exposición pública a radiaciones electromagnéticas emitidas por estaciones base de telefonía móvil (2014)
In this article, Colombian normative framework is analyzed in an integral way in relation to the exposition of the public to electromagnetic radiation issued by base stations of mobile telephones. Consequently, current legal framework was divided in seven main topics: telecommunications, the use of electromagnetic spectrum, exposition boundaries to electromagnetic fields, urban licenses, publichealth, environmental aspect, and the risk management. Likewise, nature and scope of precaution principles were assessed before the same. Finally, it was determined that Colombia does not have a legal precept, which assures thepopulation’s security before possible dangerous effects due to exposition to non ionizing radiations; the precaution principle, has not been employed to establish measures which assure citizens’ safety in relation to radioprotection